Management of yovanpidaka by vaman karma - Ritu Wadhwa; Aditi Lingayat (Wolters Kluwer Medknow Publications, 2023)
Introduction: Yovanpidaka, also known as Mukhadushika, is described under Kshudra Rogas in Ayurveda Samhitas. It can be compared with acne vulgaris. It is self-limiting in the majority but severe forms, however, lead to disfiguring scars, which can be prevented. Hence, it is essential to look out for treatment modalities which would help prevent the disfigurement caused by acne. Main Clinical Finding: A 20-year-old female presented with eruptions, pain, closed comedones, whiteheads, itching, and redness over her face for the past 2 years. Diagnosis: Yovanpidaka. Interventions: Administered Vaman with Madanphal Yoga along with milk and Yashtimadhu Phanta after proper internal oleation with Panchatikta Ghruta. Outcome and Conclusions: Marked improvement after Vaman in the signs and symptoms of the patient. Improvement in complexion was also seen.Significant result was seen in Yovanpidaka after Vaman. In cases where local treatments prove to be futile, Shodhan Chikitsa can deliver wonderful results.